Effect of Lipid Additives and Drug on the Rheological Properties of Molten Paraffin Wax, Degree of Surface Drug Coating, and Drug Release in Spray-Congealed Microparticles - Hongyi Ouyang; Audrey Yi Zheng; Paul Wan Sia Heng; Lai Wah Chan (MDPI AG, 2018)
Paraffin wax is potentially useful for producing spray-congealed drug-loaded microparticles with sustained-release and taste-masking properties. To date, there is little information about the effects of blending lipids with paraffin wax on the melt viscosity. In addition, drug particles may not be entirely coated by the paraffin wax matrix. In this study, drug-loaded paraffin wax microparticles were produced by spray-congealing, and the effects of lipid additives on the microparticle production were investigated. The influence of lipid additives (stearic acid, cetyl alcohol, or cetyl esters) and drug (paracetamol) on the rheological properties of paraffin wax were elucidated. Fourier transform-infrared spectroscopy was conducted to investigate the interactions between the blend constituents. Selected formulations were spray-congealed, and the microparticles produced were characterized for their size, drug content, degree of surface drug coating, and drug release. The viscosity of wax-lipid blends was found to be mostly lower than the weighted viscosity when interactions occurred between the blend constituents. Molten paraffin wax exhibited Newtonian flow, which was transformed to plastic flow by paracetamol and pseudoplastic flow by the lipid additive. The viscosity was decreased with lipid added. Compared to plain wax, wax-lipid blends produced smaller spray-congealed microparticles. Drug content remained high. Degree of surface drug coating and drug release were also higher. The lipid additives altered the rheological properties and hydrophobicity of the melt and are useful for modifying the microparticle properties.